Advancing the Drug Discovery and Development Process. Issue 35 (13th July 2014) - Nicolaou, K. C.
Abstract The current state of affairs in the drug discovery and development process is briefly summarized and then ways to take advantage of the ever‐increasing fundamental knowledge and technical knowhow in chemistry and biology and related disciplines are discussed. The primary motivation of this Essay is to celebrate the great achievements of chemistry, biology, and medicine and to inform and inspire students and academics to enter the field of drug discovery and development while, at the same time, continue to advance the fundamentals of their disciplines. It is also meant to encourage and catalyze multidisciplinary partnerships between academia and industry as scientists attempt to merge their often complementary interests and expertise to achieve new improvements and breakthroughs in their respective fields, and the common goal of applying them to the discovery and invention of new and better medicines, especially in areas of unmet needs.